Tension Free Vaginal Tape (TVT) for Stress Urinary Incontinence - Our Experiences (Bangladesh Journal of Urology, 2022)
Introduction: There are large numbers of adult women with troublesome urine leakage have a “stress component” to their incontinence. One common procedure to treat stress incontinence is Transvaginal Tape (TVT). In this procedure a small piece of mesh is used to support urethra. This helps to keep urine from escaping uncontrollably. This study aims at finding the outcome of TVT for treating women with SUI.Methods: We performed a prospective type of experimental study of 15 patients of 38 to 55 years old with SUI, for which they underwent TVT at Urology department, DhakaMedicalCollege hospital, from January 2014 to June 2020. Patients were selected as per selection criteria; detailed history and pre-operative investigations were done and all the women were counseled about the procedure and possible complications .We performed TVT procedure in dorsal lithotomy position under spinal anesthesia. First and second follow up was done at 6th and 12th weeks respectively. In each follow up in addition to routine checkup pad test was done, patients were asked of any urinary complain of LUTS.Result: Of the 15 patients there were no major intra-operative complications; only one woman was found to have mild bladder erosion which was treated by post-operative 14 days catheterization. Average blood loss was less than 60 ml. All the patients urinated without any complication. None required surgical re-intervention. Only one patient aged 50 years and diabetic did not improved after surgery even in 2nd follow up. Success rate was 93%. Median time to return to full domestic activities was about 4 weeks.Conclusion: TVT is safe and effective procedure for female stress urinary incontinence with an enduring, high success rate with minimal complications.Bangladesh J. Urol. 2021; 24(2): 170-174